How to improve the structural stabilities of halide perovskite quantum dots: review of various strategies to enhance the structural stabilities of halide perovskite quantum dots - Dokyum Kim; Taesun Yun; Sangmin An; Chang-Lyoul Lee (Nano Convergence, 2024)
Abstract Halide perovskites have emerged as promising materials for various optoelectronic devices because of their excellent optical and electrical properties. In particular, halide perovskite quantum dots (PQDs) have garnered considerable attention as emissive materials for light-emitting diodes (LEDs) because of their higher color purities and photoluminescence quantum yields compared to conventional inorganic quantum dots (CdSe, ZnSe, ZnS, etc.). However, PQDs exhibit poor structural stabilities in response to external stimuli (moisture, heat, etc.) owing to their inherent ionic nature. This review presents recent research trends and insights into improving the structural stabilities of PQDs. In addition, the origins of the poor structural stabilities of PQDs and various methods to overcome this drawback are discussed. The structural degradation of PQDs is mainly caused by two mechanisms: (1) defect formation on the surface of the PQDs by ligand dissociation (i.e., detachment of weakly bound ligands from the surface of PQDs), and (2) vacancy formation by halide migration in the lattices of the PQDs due to the low migration energy of halide ions. The structural stabilities of PQDs can be improved through four methods: (1) ligand modification, (2) core–shell structure, (3) crosslinking, and (4) metal doping, all of which are presented in detail herein. This review provides a comprehensive understanding of the structural stabilities and opto-electrical properties of PQDs and is expected to contribute to future research on improving the device performance of perovskite quantum dot LEDs (PeLEDs).